Timing and format of new synchronous online assessment : IIUM experience with preclinical medical students - Mohd Radzuan, Hazulin; Wan Omar, Wan Fatein Nabeila; Mat Harun, Noraihan; Mohd Noor, Mohd Fadly; Abd. Rahim, Nour El Huda; Ismail, Soraya; Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Mohamed Bakrim, Norbaiyah; Abdul Rahim, Roslina; Ahmad Affandi, Khairunisa; et al. (2020)
Introduction: The implementation of online assessment in International Islamic University Malaysia (IIUM) is debatable despite Malaysia’s promising e-readiness reported previously. However, the COVID-19 pandemic has prompted the Basic Medical Sciences (BMS) Department, Faculty of Medicine, to use iTa’LeEM, IIUM’s Moodle-based learning platform for teaching and assessment. The use of iTa’LeEM Quiz for synchronous online assessment raised various concerns in terms of timing and format of the assessment on student performance.